Manufacture of Briquettes from Baking Filter Dust (BFD) Waste and Coconut Shell Charcoal - Pramana Jaya, Aditya; Sihotang, Muhammad Sontang (Journal of Technomaterial Physics, 2022)
This research utilized baking filter dust (BFD) waste obtained from PT. INALUM., which functions as a heat retainer, is processed into briquettes with the addition of coconut shell charcoal, which has not been fully utilized. This research is also to determine the optimum quality of physical and chemical properties in good briquettes to be used as an alternative fuel. This study uses the method used is the pyrolysis method with the combustion process using a closed combustion furnace and sieving using a sieve with a size of 50-100 mesh. The quality of briquettes was analyzed using the Proximate Test, Ultimate Test, and Characterization of SEM – EDX. Furthermore, the quality test of briquettes refers to SNI 016235 2000 and the Minister of Energy and Mineral Resources No. 47 of 2006; the average moisture content of briquettes is 18.65 %, the average ash content of briquettes is 4.33 %, the average volatile matter content (volatile matters) is 13.30 %, the average fixed carbon content (fixed carbon) is 63.73 %, the average heating value is 6,200 cal/g, and the sulfur content is 49.75 % on average.